The influence of group membership and individual differences in psychopathy and perspective taking on neural responses when punishing and rewarding others. Issue 10 (18th April 2014) - Molenberghs, Pascal; Bosworth, Rebecca; Nott, Zoie; Louis, Winnifred R.; Smith, Joanne R.; Amiot, Catherine E.; Vohs, Kathleen D.; Decety, Jean
Abstract: Understanding how neural processes involved in punishing and rewarding others are altered by group membership and personality traits is critical in order to gain a better understanding of how socially important phenomena such as racial and group biases develop. Participants in an fMRI study ( n  = 48) gave rewards (money) or punishments (electroshocks) to in‐group or out‐group members. The results show that when participants rewarded others, greater activation was found in regions typically associated with receiving rewards such as the striatum and medial orbitofrontal cortex, bilaterally. Activation in those regions increased when participants rewarded in‐group compared to out‐group members. Punishment led to increased activation in regions typically associated with Theory of Mind including the medial prefrontal cortex and posterior superior temporal sulcus, as well as regions typically associated with perceiving others in pain such as the dorsal anterior cingulate cortex, anterior insula and lateral orbitofrontal cortex. Interestingly, in contrast to the findings regarding reward, activity in these regions was not moderated by whether the target of the punishment was an in‐ or out‐group member. Additional regression analysis revealed that participants who have low perspective taking skills and higher levels of psychopathy showed less activation in the brain regions identified when punishing others, especially when they were out‐group members. In sum, when an individual is personally responsible for delivering rewards and punishments to others, in‐group bias is stronger for reward allocation than punishments, marking the first neuroscientific evidence of this dissociation. Hum Brain Mapp 35:4989–4999, 2014 . © 2014 Wiley Periodicals, Inc .